Fertility Status of Plantation Soils - Rajamannar, A.; Krishnamoorthy, K. K. (Indian Forester, 1982)
Plantation soils of Kodaikanal and Kumuli were studied for their fertility status. The soils collected from different profiles were subjected to various physico chemical analysis. Soils are laterite in origin and their pH ranges from 4.6 to 6.1. Surface soils show high amount of moisture and are also rich in organic matter. Surface soils are higher in total and available nurients of N, P and K content. Cation exchange capacity and other cations are also higher in surface soils. The nutrient content decreased progressively with depth. The study indicates that these well drained plantation soils are rich in humus and are highly fertile.